Customer Perception and Price Sensitivity: A Study of Muslim Consumers Behavior on Shopee - Nurfitriani Nurfitriani; Moh Agus Nugroho (Jurnal Internasional Ekonomi Islam, 2023)
The surge in online shopping is on the rise, yet engaging in online selling comes with challenges. Vendors utilizing online platforms like Shopee must grasp the factors that sway buying choices. This becomes crucial as they strive to encourage consumers to purchase products they cannot physically interact with. While numerous investigations have been conducted, there exists an untouched area about Shopee consumers in Palu City. Previous research has revealed that both pricing and customer reviews have an impact on purchase decisions. Conversely, some studies negate their influence. Hence, the present study endeavors to elucidate the extent to which pricing and customer reviews shape the purchasing determinations of Shopee consumers, specifically in Palu City. This research sheds light on the subject by employing a questionnaire-based survey method and utilizing the SPSS software for analysis. Findings indicate that both factors, taken together or individually, wield a notable influence on the purchasing judgments made by Shopee consumers in Palu City. Given that purchasing choices stand as a metric for gauging marketing achievements, the insights from this study are anticipated to offer valuable guidance to digital marketplace sellers when devising their marketing strategies.